Willingness to receive a COVID-19 booster vaccine: the role of health literacy and the 7Cs model. - Falcon, María; Rodríguez-Blázquez, Carmen; Fernández-Gutiérrez, Martina; Forjaz, Maria João; Bas-Sarmiento, Pilar; Romay-Barja, María (European Journal of Public Health, 2026)
Vaccination is a modifiable behaviour resulting from a complex decision-making process influenced by a wide range of factors, including the '7Cs' model (confidence, complacency, constraints, calculation, collective responsibility, compliance, and conspiracy) and the ability to find, understand, evaluate and use vaccine information. This work aimed to analyse the intention to receive a booster dose of the COVID-19 vaccine in Spain in the subsequent rollout of the COVID-19 vaccination campaign and how it was influenced by COVID-19 vaccination health literacy and the '7Cs' determinants of vaccine hesitancy. A descriptive cross-sectional study was conducted in February 2022 using an online survey. The sample comprised 1067 participants aged 18 or older, representative of the Spanish general population. Willingness to receive an additional booster dose of the COVID-19 vaccine was assessed using a single yes/no answer question. Determinants of vaccine readiness were evaluated through seven statements aligned with the 7Cs model, adapted to the COVID-19 context. A multivariable logistic regression showed that vaccination intention was influenced by Confidence (OR = 3.79; 95% CI = 2.58–5.58), Calculation (OR = 0.63; 95% CI = 0.45–0.90), Collective Responsibility (OR = 0.52; 95% CI = 0.32–0.86), Compliance (OR = 2.10; 95% CI = 1.42–3.09), Conspiracy (OR = 0.46; 95% CI = 0.29–0.74), and vaccine related HL (OR = 1.03; 95% CI = 1.02–1.06). Fostering vaccination health literacy, strengthening trust in science and health professionals, fighting misinformation and enhancing collective responsibility are relevant aspects for designing effective vaccination campaigns.